High survival in young patients using a second generation uncemented total hip replacement - Streit, Marcus R.; Körber, Matthias; Merle, Christian; Gotterbarm, Tobias; Ewerbeck, Volker (International orthopaedics, 2012)
PurposeWhilst excellent long-term results with contemporary uncemented stems have been reported for total hip arthroplasty in young patients, the survival rates for the whole reconstruction are often compromised by high failure rates on the acetabular site due to peri-acetabular osteolysis and accelerated wear.MethodsIn patients 60 years old or younger, we retrospectively reviewed the results at a minimum of ten years of 89 consecutive uncemented total hip replacements in 88 patients using the press-fit Fitmore acetabular component in combination with the CLS Spotorno stem and a 28-mm Metasul metal-on-metal articulation or a 28-mm alumina ceramic on conventional polyethylene bearing. The mean age at the time of surgery was 49 years (range, 25-60). The mean clinical and radiological follow-up was 12 years (range, 10-15).ResultsSix patients (six hips) died and two patients (two hips) were lost to follow-up. Five hips were revised: one for deep infection, one for peri-prosthetic femoral fracture, and one for aseptic stem loosening. In two hips an isolated revision of the acetabular liner was performed (one for recurrent dislocation and one for unexplained pain). No revision was performed for accelerated wear, osteolysis or aseptic loosening of the acetabular shell. We could not detect peri-acetabular osteolysis visible on plain radiographs in those hips evaluated radiographically. The Kaplan-Meier survival with revision for any reason as the endpoint was 94% (95% confidence interval, 86-97) at 12 years.ConclusionsThe survival rates and the radiological outcomes with this implant combination in this young and active patient group are encouraging when compared to the results reported for other uncemented cups in this age group.